Structure and function of a peptide pheromone family that stimulate the vomeronasal sensory system in mice. (11th August 2014) - Abe, Takayuki; Touhara, Kazushige
Abstract : Mammals use pheromones to communicate with other animals of the same species. In mice, the VNO (vomeronasal organ) has a pivotal role in pheromone detection. We discovered a 7 kDa peptide, ESP1 (exocrine-gland-secreting peptide 1), in tear fluids from male mice that enhances the sexual behaviour of female mice via the VNO. NMR studies demonstrate that ESP1 adopts a compact structure with a helical fold stabilized by an intramolecular disulfide bridge. Functional analysis in combination with docking simulation indicates that ESP1 is recognized by a specific G-protein-coupled vomeronasal receptor, V2Rp5, via charge–charge interactions in the large extracellular region of the receptor. ESP1 is a member of the ESP family, which comprises 38 homologous genes in mice, and some of these genes are expressed in a sex- or age-dependent manner. Most recently, ESP22 was found to be released specifically in juvenile tear fluids and to inhibit the sexual behaviour of adult male mice. These studies demonstrate that peptide pheromones are used for chemical communication in mice, and they indicate a structural basis for the narrowly tuned perception of mammalian peptide pheromones by vomeronasal receptors.